APPLICATION OF ISLAMIC FINANCIAL INSTRUMENTS IN THE INSURANCE MARKET - Dildora Abdusalimovna Muradova (Ecominds Press, 2025)
This article examines the application of Islamic financial instruments in the insurance market. The article provides a detailed explanation of the essence of the takaful system, its differences from conventional insurance, historical development, main models, and practical aspects. The article analyzes takaful models such as mudaraba, wakala, waqf, and hybrid models, and demonstrates their practical application through examples. Furthermore, the article highlights the specific features of various takaful products, including vehicle, property, health, education, pension, and life takaful. Based on statistical data, the article describes the current state and future prospects of the global takaful market and analyzes the possibilities of implementing takaful in Uzbekistan.
Keywords: Islamic finance, takaful, insurance, mudaraba, wakala, waqf, interest-free insurance, Islamic financial instruments, mutual assistance, halal investments, Islamic insurance products.